A formação do Engenheiro Químico no contexto da Indústria 4.0 - Pinto, Regina Carneiro (Universidade Federal de São Carlos, 2020)
In 2018, the Federação das Indústrias do Estado de São Paulo (Fiesp) carried out a survey to identify the degree of knowledge of Brazilian companies related to the concept of industry 4.0 and the challenges to be faced for its adoption. Two hundred and twenty-seven companies were interviewed, 55% of which were small, 30% medium and 15% large. Initially, 32% of companies said they did not know the terms "fourth industrial revolution", "industry 4.0" or "advanced manufacturing". For the remaining 68%, some other results were obtained: 90% agree that the fourth industrial revolution will have positive impacts on productivity, 67% expect to feel a medium impact with the implementation of advanced manufacturing, but only 5% feel very prepared for the transformations to be faced. Asked about the biggest challenges, que workforce qualification was one of the mentioned points. Since chemical engineering is so close to industry, reflection on the consequences of the fourth industrial revolution in the graduation is necessary. A demonstration of the importance of the theme is that updating regarding innovation, science and technology are topics directly cited in Resolução CNE / CES nº2, of April 24, 2019, which establishes the national curriculum guidelines for the undergraduate engineering course. As a study tool, a research was carried out with graduates of the chemical engineering course at Universidade Federal de São Carlos (UFSCar). All respondents are inserted in the job market in functions directly related to the area of performance of the chemical engineer and answered questions related to the tools used in their daily work and the challenges faced in their professional performance. In addition to the research, the undergraduate curriculum offered by the Department of Chemical Engineering at UFSCar was studied in order to find options for the insertion of new themes in the course structure, using as a resource also the comparison with curricular grades of other universities in the country. The modernization proposals were developed following two paths: the adaptation of existing subjects and the addition of new subjects, helping with ideas to restructure the curriculum.
The formation of the Chemical Engineer in the context of Industry 4.0
Keywords: Indústria 4.0; 4.0 Industry; Ensino; Engenharia Química; Chemical Engineering; ENGENHARIAS::ENGENHARIA QUIMICA